Analysis of Influence of Cable Injury on Static Performance of Cable-Stayed Bridge - Shoushan Cheng; Tongning Wang; Xin Cui; Guoquan Hai; Yitao Zhang; Yongzheng Yu (Buildings, 2025)
Under prolonged loading and various environmental factors, the performance of stay cables gradually deteriorates, which impacts the safety of the bridge structure. To investigate the influence of cable damage on the static performance of cable-stayed bridges, a finite element model of a cable-stayed bridge with damaged cables was established. The element death method is used to simulate cable damage, examining the impact of various damage scenarios on the static performance of the cable-stayed bridge. The objective is to identify cable locations that have a greater impact on the structure, providing a basis for assessing the bridge’s safety and developing cable replacement strategies. The research indicates that damage to long cables has a more significant impact on the static performance of the cable-stayed bridge compared to damage to short cables. Additionally, damage to the side span cables has a more pronounced effect on the structure than damage to the mid-span cables. The influence of cable damage on cable forces is primarily reflected on the same side of the cable plane within the same bridge tower as the damaged cable. Changes in cable forces result in variations in the deflection of the main girder and the displacement of the main tower. When multiple cables are damaged, the impact on the static performance of the structure is similar to that of single-cable damage. In instances of longitudinal symmetric damage and adjacent cable impairment, the cables transition into a critical state, resulting in more pronounced alterations in the deflection of the main girder and the displacement of the main tower. Original symmetric damage has a relatively small impact on the static performance of the entire bridge, so it is recommended to adopt a symmetric approach for cable replacement projects. Considering the impact of damage to a single cable and multiple cables on the static structure, it is possible to initially determine the location and extent of the cable damage. Based on the damage patterns, a cable replacement plan can be designed. It is recommended to use a symmetry-based approach for the cable replacement, as this method results in minimal impact on the overall static performance of the bridge, thereby ensuring the safety of the bridge structure.